THE EFFECTIVENESS OF REMINDER MESSAGES IN INCREASING COMPLIANCE WITH ARV DRUG IN HIV/AIDS PATIENTS - Nadia Salsabila Fauziah; Dewi Purnamawati (Muhammadiyah International Public Health and Medicine Proceeding, 2022)
HIV (Human Immunodeficiency Virus) and AIDS (Acquired Immune Deficiency Syndrome) are global health problems that cause morbidity and mortality. Non-adherence in treatment is a problem of the failure of HIV/AIDS patients in undergoing ARV treatment. One of the efforts that can be done with a Short Message Service (SMS) reminder is to determine the effectiveness of SMS reminders in improving medication adherence to ARV in people living with HIV/AIDS. His study uses a narrative literature review method with critical, objective, and comprehensive analysis. The keywords are taken from electronic databases ProQuest, Science Direct, PubMed, and Google Scholar. The search results on the data found as many as 244 articles published from 2016 – 2021, after which a full-text review of the feasibility of the articles was carried out and had articles for the literature review and obtained 6 articles that met the criteria and were relevant. In conclusion, SMS Reminders can facilitate interaction between patients and health care providers in increasing adherence to ARV treatment in people with HIV. It is recommended to use SMS reminders for more variety of problems in HIV patients so that this study can be helpful for HIV patients in general.